Oxfordshire Childrens Diabetes - The Primary Schools Intervention Programme. Issue 1 (17th May 2013) - Pal, Rani; Edge, Julie
Abstract: Poorly controlled diabetes adversely affects a child's education, with concentration difficulties, alterations in mood, behaviour and fatigue associated with high or low blood glucose levels. Between years 2004-6 we started all toddlers and children on intensive insulin regimens (multiple dose injection or pump) making it imperative that they received support during the school day. This required close monitoring of blood glucose levels and counting carbohydrate intake to adjust rapid-acting insulin dose or pump bolus at every meal. We report our experience of formulating a sustainable structure of support in primary schools based on trained volunteers who partake in the daily 'Individualised Care Plan (ICP)'. After overcoming multiple barriers, an acceptable system was negotiated with our Primary Care Trust (PCT) and Local Education Authority (LEA). In 2009, the PCT confirmed 3 years funding for a Paediatric Diabetes specialist nurse (PDSN) for schools. In 2010, the first full school year with agreed protocols was in place. By July 2012, our nurses had trained a total of 342 volunteers who provide care for 132 children. The Oxfordshire Schools Intervention Programme ensures that legal obligations are met. A risk assessment allows the LEA to provide indemnity to their school staff to give injections and do blood tests, after training and competency sign-off by a PDSN. Parents, volunteers and PDSN jointly agree a comprehensive 'ICP' and utilise a hand-held communication record book. Diabetes control improved (age 4-11 years cohort from 2004 onwards: Mean (SD) HbA1c in 2001-4 = 8.38 (1.09)%; in 2005-8 = 7.74 (0.81)%; in 2009-12 = 7.58 (0.69)%; ANOVA p<0.001). This requires 500-1000 hours of DSN time to train/retrain/problem-solve annually (approximately 5-10days per month). The cost-benefits are discussed. We advocate that our programme supports each child's ICP, use of intensive insulin regimes in school-day and reassures parents that schools can deliver this safely.